SCIENTIFIC AND METHODOLOGICAL SUPPORT OF THE FORMATION OF THE FUTURE DOCTORS’ COMMUNICATIVE CULTURE - Youssef, V (Continuing Professional Education: Theory and Practice, 2019)
The article is devoted to the problem of formation of the communicative culture of the future doctors. Analyzed the conceptual approaches to the problem of current research communication training students. Developed and experimentally verified the scientific and methodological support of the formation of the communicative culture of the future doctors in the study of humanities and social sciences. The comparative analysis of the results, that have been obtained in the process of the determining the initial level of the student‘s communicative culture at the stage of final experimental data, allowes to observe the positive dynamics. So the scientifical and methodological support of the future physicians‘ training for the professional and pedagogical communication seamlessly combines the modern information and communication means with the traditional forms of the interpersonal communication that implement through the modular information and communication technology as one of the example of the integrated (combined) technological processes. This support provides the active creative communicative activity of each student in the pedagogical process